High-power diode lasers with in-situ-structured lateral current blocking for improved threshold, efficiency and brightness. (1st January 2023) - Elattar, M; Brox, O; Della Casa, P; Mogilatenko, A; Maaßdorf, A; Martin, D; Wenzel, H; Knigge, A; Weyers, M; Crump, P
Abstract: We present high-power GaAs-based broad-area diode lasers with a novel variant of the enhanced self-aligned lateral structure 'eSAS', having a strongly reduced lasing threshold and improved peak conversion efficiency and beam quality in comparison to their standard gain-guided counterparts. To realize this new variant (eSAS-V2), a two-step epitaxial growth process involving in situ etching is used to integrate current-blocking layers, optimized for tunnel current suppression, within the p-Al0.8 GaAs cladding layer of an extreme-triple-asymmetric epitaxial structure with a thin p-side waveguide. The blocking layers are thus in close proximity to the active zone, resulting in strong suppression of current spreading and lateral carrier accumulation. eSAS-V2 devices with 4 mm resonator length and varying stripe widths are characterized and compared to previous eSAS variant (eSAS-V1) as well as gain-guided reference devices, all having the same dimensions and epitaxial structure. Measurement results show that the new eSAS-V2 variant eliminates an estimated 89% of lateral current spreading, resulting in a strong threshold current reduction of 29% at 90 μ m stripe width, while slope and series resistance are broadly unchanged. The novel eSAS-V2 devices also maintain high conversion efficiency up to high continuous-wave optical power, with an exemplary 90 μ m device having 51.5% at 20 W. Near-field width is significantly narrowed in both eSAS variants, but eSAS-V2 exhibits a wider far-field angle, consistent with the presence of index guiding. Nonetheless, eSAS-V2 achieves higher beam quality and lateral brightness than gain-guided reference devices, but the index guiding in this realization prevents it from surpassing eSAS-V1. Overall, the different performance benefits of the eSAS approach are clearly demonstrated.